Cho B=1+3+32+33+...+31991
CMR B\(⋮\)41
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 8⁸ + 2²⁰
= (2³)⁸ + 2²⁰
= 2²⁴ + 2²⁰
= 2²⁰.(2⁴ + 1)
= 2²⁰.17 ⋮ 17
Vậy A ⋮ 17
A=11+22+33+44
=33+77
=110
B=14+23+32+41
=37+73
=110
VÌ 110=110 NÊN A =B
A = 11 + 22 + 33 + 44
= 33 + 33 + 44
= 66 + 44
= 110
B = 14 + 23 + 32 + 41
= 37 + 73
= 110
Vậy A = B ( = 110 )
a, 2 3 x + 5 2 x = 2 5 2 + 2 3 - 33
8x+25x = 33
33x = 33
x = 1
b, 260 : x + 4 = 5 2 3 + 5 - 3 3 2 + 2 2
260:(x+4) = 5.13–3.13
x+4 = 260:26
x+4 = 10
x = 6
c, 720 : [ 41 - 2 x - 5 ] = 2 3 . 5
41–(2x–5) = 720:40
2x–5 = 41–18
2x = 28
x = 14
d, 3 2 - 2 x - 12 + 35 = 5 2 + 279 : 3 2
7(x–12)+35 = 56
7(x–12) = 21
x–12 = 3
x = 15
A = 1 + 3 + 32 + 33 + ... + 3100
3A = 3 + 32 + 33 +34+ .... + 3101
3A - A = (3 + 32 + 34 + ... + 3101) - (1 + 3 + 32 + 33 + ... + 3100)
2A = 3 + 32 + 34 + ... + 3101 - 1 - 3 - 32 - 33 - ... - 3100
2A = (3 - 3) + (32 - 32) + ... + (3100 - 3100) + (3101 - 1)
2A = 3101 - 1
A = \(\dfrac{3^{101}-1}{2}\)
Lời giải:
$A=1+3+3^2+3^3+...+3^{2021}$
$3A=3+3^2+3^3+...+3^{2022}$
$\Rightarrow 3A-A=(3+3^2+3^3+...+3^{2022}) - (1+3+3^2+3^3+...+3^{2021})$
$\Rightarrow 2A=3^{2022}-1$
$\Rightarrow A=\frac{3^{2022}-1}{2}$
$B-A=\frac{3^{2022}}{2}-\frac{3^{2022}-1}{2}=\frac{1}{2}$
\(B=3+3^2+3^3+...+3^{100}\)
\(=3+\left(3^2+3^3+3^4\right)+...+\left(3^{98}+3^{99}+3^{100}\right)\)
\(=3+3^2\left(1+3+3^2\right)+...+3^{98}\left(1+3+3^2\right)\)
\(=3+3^2.13+...+3^{98}.13\)
\(=3+13\left(3^2+...+3^{98}\right)\)
\(\Rightarrow B⋮̸13\)
\(\Rightarrow B:13\) dư 3.
\(A=\dfrac{1}{3}+\dfrac{1}{3^2}+\dfrac{1}{3^3}+\dfrac{1}{3^4}+...+\dfrac{1}{3^{99}}\)
\(\Rightarrow\dfrac{A}{3}=\dfrac{1}{3^2}+\dfrac{1}{3^3}+\dfrac{1}{3^4}+...+\dfrac{1}{3^{100}}\)
\(\Rightarrow A-\dfrac{A}{3}=\dfrac{2A}{3}=\left(\dfrac{1}{3}+\dfrac{1}{3^2}+\dfrac{1}{3^3}+...+\dfrac{1}{3^{99}}\right)-\left(\dfrac{1}{3^2}+\dfrac{1}{3^3}+\dfrac{1}{3^4}+...+\dfrac{1}{3^{100}}\right)\)
\(\Rightarrow\dfrac{2A}{3}=\left(\dfrac{1}{3^2}-\dfrac{1}{3^2}\right)+\left(\dfrac{1}{3^3}-\dfrac{1}{3^3}\right)+...+\left(\dfrac{1}{3^{99}}-\dfrac{1}{3^{99}}\right)+\left(\dfrac{1}{3}-\dfrac{1}{3^{100}}\right)=\dfrac{1}{3}-\dfrac{1}{3^{100}}\)
\(\Rightarrow2A=3\cdot\left(\dfrac{1}{3}-\dfrac{1}{3^{100}}\right)\)
\(\Rightarrow\text{A}=\dfrac{1-\dfrac{1}{3^{99}}}{2}\)
\(\Rightarrow A=\dfrac{1}{2}-\dfrac{1}{2.3^{99}}< \dfrac{1}{2}\)